KEMAMPUAN BELANJA PEMERINTAH DAN PERTUMBUHAN EKONOMI DALAM MENURUNKAN TINGKAT KEMISKINAN: BUKTI EMPIRIS DARI SUMATERA DAN JAWA - Roosemarina Anggraini Rambe; Purmini Purmini (Convergence: The Journal of Economic Development, 2020)
The objective of the research is to analyze the effect of government expenditure, economic growth and previous poverty rate on the current poverty rate in Java and Sumatra. The data set was 267 local governments in year 2017.  The method used in this research was multiple regression. Results show that government expenditure and economic growth affect significantly positively the poverty rate. While the previous poverty rate has negative effect on the current poverty rate. Local governments in Java and Sumatra should make appropriate programmes and activities and allocate optimally their expenditures to build the new SMEs and improve the existing SMEs abilities in order to reduce the poverty rate. Keywords :  A Previous Poverty Rate 1, Economic Growth 2, Government Expenditure 3, Poverty Rate 4